Nursing satisfaction and job enrichment in Turkey - (:unkn) unknown (SAGE PUBLICATIONS INC, 2006)
Survey research was conducted with the aim of better understanding nurses' perceptions of organizational factors which relate to their job satisfaction and motivation in Turkey. Nurses (N = 290) who were employed at a training and research hospital, part of the Turkish Republic Ministry of Health, were included. The questionnaire used was developed for this study based on Hackman and Oldman's job enrichment theory. The results showed that only one third of the nurse leaders and one in five of the staff nurses reported being satisfied with their job. The participants saw the five core job dimensions of Hackman and Oldman's work design model: skill variety, task identity, task significance, autonomy, and feedback as important for nurses. Nursing was described by the participants as hard and challenging, but they also found it meaningful and said that it gave them the opportunity to use their skills and abilities.
Keywords: job enrichment; nursing